CRECIMIENTO DE GORRINOS PROVENIENTES DE MADRES CON Y SIN ANTECEDENTES DE VACUNACIÓN CONTRA Mycoplasma hyopneumoniae - Cisneros S., Jannet (2005)
The aim of the study was to evaluate body weight gain of piglets coming from vaccinated and not vaccinated sows against Mycoplasma hyopneumoniae. Two groups of four sows each from a herd positive to M. hyopneumoniae were randomly selected. One group was vaccinated with a bacterin against M. hyopneumoniae at day 85 of gestation, while the other was kept as control. After parturition, 30 piglets (50% female and 50% male) from each group of sows were selected and weighed at weaning (19 days of age) and at slaughter (149 days of age). Food intake per group was daily recorded. In addition, the degree of lung lesions at slaughter in a scale of 0-6 was evaluated. No significant statistical difference was found in body growth (final body weight and body weight gain) as well as in lung lesions between groups or sex.